Estudo das encostas ocupadas desordenadamente na cidade do Rio de Janeiro: a favela do Vidigal - Sobreira, Frederico Garcia (1989)
The disordered development, the economic conditions of the population, historical factors as well as the lack of suitable areas for occupation have led to a chaotic framework of the urban structure in Rio de Janeiro. Abrupt hills and swampy areas have been gradually occupied by the low income people who try to solve their prompt livin and transportation problems. As a consequence, natural problems which exist in such areas have become more serious with even the risk of life of the population. This work presents a contribuition to the geological-geothecnical study thecnique of disordered occupied slopes (favelas). A versatile character of the metodological directive is due to unequal conditions in each one of such places. A map of soil use has been obtained from a detailed geological-geothecnical mapping (1:2.000 scale) from a declivity map and from local existing problems. This map purposes to give directions and to organize the occupation by indicating urbanizable, partly urbanizable, risk and preservation areas. The locality choosen for such study was the "favela do Vidigal", at the "Dois Irmãos" hill, south zone of the Rio de Janeiro city. Due to several existing technical situations and the kinds of occupation, this area has provided a general application work.